Sulcus fixated injectable toric intraocular lens to correct astigmatism following penetrating keratoplasty in a pseudophakic eye. (11th October 2010) - Srinivasan, Sathish; Lyall, Douglas; Watt, John
Abstract : A 56-year-old Caucasian male was referred to the corneal service for the management of post penetrating keratoplasty (PK) astigmatism in his right eye. He had also previously undergone trabeculectomy and cataract surgery in the same eye. Corneal topography showed high postoperative astigmatism of 8.74 dioptres. He was intolerant to contact lens wear and could not tolerate spectacle correction due to high anisometropia. He proceeded to undergo a secondary 'piggyback' toric intraocular lens (IOL) insertion procedure with an improvement in his best corrected visual acuity to 6/9. With the decrease in anisometropia he was able to tolerate a full spectacle correction. We report the use of a new injectable sulcus fixated toric piggyback IOL for the correction of post PK astigmatism in a pseudophakic eye. To the best of our knowledge this is the first report on the use of this new 'add on' IOL for this clinical condition.